'Almost a Statesman': East Central Europe's geography experts and the Paris Peace Conference. (October 2022) - Górny, Maciej
Abstract: Although the centenary of the 1919–1920 Paris Peace Conference reignited interest in this pivotal post-war event, the perspective of East Central European geographical sciences remains little investigated. In 1918 and 1919, rather unexpectedly, geography turned out to be a confidante of the knowledge that shaped the future of the world, and it was geographers from new states that emerged in the Eastern and South-Eastern part of the continent that largely contributed to this development. The article assesses the limits of their impact while it also characterises the tensions between their understanding of 'science' and their nationalism. Highlights: Geographers played a key role in post-WWI diplomatic conferences. Experts' political role in border-making exceeded that of the local politicians. Peace Conference was the field for methodological innovation in geography. ECE's experts belonged to the main authors of the said innovation. ECE played pivotal role in the post-WWI reflection on border-making.